Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Cooperative Learning Tipe Make A Match Dalam Pembelajaran Tari Di SMK Negeri 3 Padang - Pebrina Sapitri; Indrayuda Indrayuda; Fuji Astuti (SENDRATASIK UNP, 2019)
This article aims to describe and explain about the learning outcomes of students in class X of SMK 3 Padang by using Cooperative Learning model, Type Make a Match. This type of research is Classroom Action Resarch. This research was conducted in 2 cycles, three meetings for first cycle and two meetings for second cycle. At the end of the cycle the students were given a test. For collecting the data, the witer used field notes, documentation and written tests. The analysis of learning activities calculated by percentage. Learning activities for students involved during the learning. The result of the study shows that using the Make a Match type with Cooperative Learning model can be used to help students in learning activities in Cultural Arts subject, especially dancing at SMK 3 Padang. Student learning outcomes in cycle II are more increase than the learning outcomes of cycle I. The first cycle was proved that the learning outcomes of class X BDP students in the first cycle got an average score of 65.71 with the criteria "Enough". The second cycle with an average score of 86.16 can be categorized as "Good". It can be concluded that there was an improvement in using The learning outcomes used the Make A Match type with Cooperative Learning model and the target was reached successfully.